Industrial sustainability: Transition support handbook and compliance of small companies in the textile sector (ModaPalavra e-periódico, 2023)
This research presents the process of developing a transition support manual for industrial sustainability of small and medium enterprises, seeking to contribute to better waste management and adoption of eco -efficient and circular processes so important in reducing negative impact and maintaining balance of planet. Since the Industrial Revolution, the textile sector has undergone several changes, but some processes remain unchanged; even with technological evolutions. Industry grows natural resources, aiming at increasing scalability of production over the reduction in product quality and life; along with increased negative impact on the environment.
Keywords: industrial sustainability; transition; support handbook